2002
DOI: 10.1007/s00134-002-1347-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of propofol on airway pressures generated by magnetic stimulation of the phrenic nerves

Abstract: Propofol does reduce the effectiveness with which diaphragmatic contraction produces changes of pressure in the airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
3
1
1
Order By: Relevance
“…These results show that TwPdi is transiently inhibited by propofol at standard induction dose. Our result is similar to that of Shaw and colleagues, 19 who stimulated the phrenic nerve using supramaximal magnetic stimuli before and immediately after induction of propofol in 11 subjects. The change in airway pressure at the mouth (TwPmo) produced by the resulting diaphragmatic contraction was monitored instead of TwPdi, with a significant decline of TwPmo by 14.2%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results show that TwPdi is transiently inhibited by propofol at standard induction dose. Our result is similar to that of Shaw and colleagues, 19 who stimulated the phrenic nerve using supramaximal magnetic stimuli before and immediately after induction of propofol in 11 subjects. The change in airway pressure at the mouth (TwPmo) produced by the resulting diaphragmatic contraction was monitored instead of TwPdi, with a significant decline of TwPmo by 14.2%.…”
Section: Discussionsupporting
confidence: 91%
“…However, a similar study demonstrated that the apparent fall in diaphragm strength is not a function of the change in lung volume on induction with propofol. 19 In some other studies, a fall in diaphragm strength leads to a fall in lung volume, and a fall in lung volume tends to an increase in twitch strength. 26 -28 Therefore, we do not think the depressed twitch strength in our study is caused by a fall in lung volume.…”
Section: Discussionmentioning
confidence: 90%
“…The complex relationships between lung volume changes, mechanics of the chest wall, diaphragm and abdomen make the assessment of the effects of anaesthetic agents on the diaphragm appreciably difficult. However, two studies have demonstrated the inhibitory effects of propofol on diaphragmatic contractility in patients during general anaesthesia 15,16 . We are not aware of any studies of the effects of propofol on the neuromuscular function of the rib cage, but if we hypothesise that data from other striated muscle could also be valid for the chest wall, Dueck and colleagues' paper on propofol's relaxant properties on the abductor pollicis muscle studied by stimulating the median nerve could be relevant 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides central effects, propofol also has direct inhibitory effects on diaphragmatic contractility in humans (624,782). Shaw et al (625) stimulated the phrenic nerves supramaximally with magnetic coils and measured the change of airway pressure at the mouth produced by the resulting diaphragmatic contraction.…”
Section: Effects On the Acute Hypoxic Ventilatory Responsementioning
confidence: 99%